Personalizing the state : the anthropology of law, politics, and welfare in austerity Britain - Koch, Insa Lee (Oxford : Oxford University Press, 2019)
Starting with penal populism, this text examines a paradox: the illiberal turn that liberal democracy has taken. Based on ethnographic fieldwork on a housing estate, it moves from why liberal democracy has taken a punitive turn, to what democracy means to these residents and how they experience their daily engagements with the state.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 8, 2019).
Keywords: Marginality, Social -- Great Britain; Great Britain -- Social conditions; Great Britain -- Economic conditions; Great Britain -- Politics and government; Society; Society & culture: general